A Review of the Toxicity and Phytochemistry of Medicinal Plant Species Used by Herbalists in Treating People Living With HIV/AIDS in Uganda - Anywar, G.; Kakudidi, E.; Byamukama, R.; Mukonzo, J.; Schubert, A.; Oryem-Origa, H.; Jassoy, C. (Frontiers in Pharmacology, 2021)
Introduction: Despite concerns about toxicity, potentially harmful effects and herb-drug interactions, the use of herbal medicines remains widely practiced by people living with HIV/AIDS (PLHIV) in Uganda. Objective: The objective of paper was to comprehensively review the literature on the toxicity and chemical composition of commonly used medicinal plant species in treating PLHIV in Uganda. Methods: We reviewed relevant published articles and books between over the last sixty years, thesis, dissertations, patents, and other reports on ethnobotany, antiviral/anti-HIV activity, toxicity, phytochemistry of Vachellia hockii, Albizia coriaria, Bridelia micrantha, Cryptolepsis sanguinolenta, Erythrina abyssinica, Gardenia ternifolia, Gymnosporia senegalensis, Psorospermum febrifugium, Securidaca longipendunculata, Warburgia ugandensis and Zanthoxylum chalybeum was conducted and their synonyms. We searched databases and search engines including PubMed, Web of Science, Scopus, Science Direct and Google Scholar Discussion: Most of the plant species reviewed apart from P. febrifugium, S. longipedunculata and C. sanguinolenta lacked detailed phytochemical analyses as well as the quantification and characterization of their constituents. Crude plant extracts were the most commonly used. However, purified/single component extracts from different plant parts were also used in some studies. The U87 human glioblastoma was the most commonly used cell line. Water, ethanol, methanol and DMSO were the commonest solvents used. In some instances, isolated purified compounds/extracts such as Cryptolepine and Psorospermin were used. Conclusion: Cytotoxicity varied with cell type, solvent and extract type used making it difficult for direct comparison of the plant species. Five of the eleven plant species namely, A. coriaria, C. sanguinolenta, G. ternifolia, P. febrifugium and Z. chalybeum had no cytotoxicity studies in animal models. For the remaining six plant species, the crude aqueous and ethanol extracts were mainly used in acute oral toxicity studies in mice. Herbalists reported only A. coriaria and W. ugandensis to cause toxic side effects in humans. However, selectively cytotoxic plant extracts can potentially be beneficial as anticancer or anti-tumour drugs.